Crossover from the coffee-ring effect to the uniform deposit caused by irreversible cluster-cluster aggregation - Crivoi, Alexandru (2015)
The coffee-ring effect for particle deposition near the three-phase line after drying a pinned sessile colloidal droplet has been suppressed or attenuated in many recent studies. However, there have been few attempts to simulate the mitigation of the effect in the presence of strong particle-particle attraction forces. We develop a three-dimensional stochastic model to investigate the drying process of a pinned colloidal sessile droplet by considering the sticking between particles, which was observed in the experiments. The Monte Carlo simulation results show that by solely promoting the particle-particle attraction in the model, the final deposit shape is transformed from the coffee ring to the uniform film deposition. This phenomenon is modeled using the colloidal aggregation technique and explained by the “Tetris principle,” meaning that unevenly shaped or branched particle clusters rapidly build up a sparse structure spanning throughout the entire domain in the drying process. The influence of the controlled parameters is analyzed as well. The simulation is reflected by the drying patterns of the nanofluid droplets through the surfactant control in the experiments.